(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study examines the impact of Corporate Social Responsibility (CSR) on poverty alleviation in Cross River State, Nigeria, focusing on the effectiveness of CSR initiatives in emerging economies. Despite some positive perceptions, approximately 41.75% of respondents believe these initiatives have no impact. The study employs a mixed-methods approach, combining surveys and interviews with 400 respondents, including community stakeholders and CSR practitioners. Findings show a moderate correlation (R = 0.67, R² = 0.45) between CSR effectiveness and poverty alleviation. Key challenges include insufficient funding (31.75%), poor community engagement (29.75%), and low CSR awareness (18.25%). The study recommends enhancing collaboration between corporations and local organizations, increasing awareness, and seeking government support to strengthen CSR initiatives. Addressing these challenges can improve CSR’s impact on poverty alleviation, contributing to sustainable development in Cross River State and similar economies.